Sunjeev Sahota’s fictions of failed cosmopolitan conviviality - Mendes, Ana Cristina (2019)
Sunjeev Sahota’s postcolonial fiction explores why and how young, male, working-class British Asians in post-industrial urban spaces in the Midlands of the UK are drawn to radicalization and militant interpretations of Islam. Sahota’s writings emerge from a young but remarkably dynamic literary subgenre of British Asian literary fiction which surged onto the literary scene in the wake of Salman Rushdie’s Midnight’s Children (1981). Sahota’s work is set in Sheffield; his debut novel, Ours are the Streets (2011), which clinched him a place on the Granta Best of Young British Novelists list, was inspired by the 7/7 bombings and narrated the disaffection of Imtiaz Raina, a would-be suicide British bomber of Pakistani ancestry; his second novel, The Year of the Runaways, was shortlisted for the 2015 Man Booker Prize. Sahota’s novels stand as a critique of cosmopolitanism, portraying a ‘crisis of conviviality’ (Georgiou 2017) within the metropolis. In ways that will be detailed through close reading of Ours are the Streets, Sahota’s 2011 novel mediates and explores the opacities and inconsistencies of present cosmopolitan experiences, anachronistically highlighted by the United States presidential election of Donald Trump in 2016 and the current post-Brexit cultural shock. This failed cosmopolitan conviviality is deeply tied up with issues around political literacy and class, as well as intolerance and Islamophobia, which have given rise to new-old forms of right-wing extremisms invested in combating neoliberal globalism (visible, for example, in the manifesto of the Traditionalist Worker Party in the US). The Trump election and Brexit, which came after the publication of Ours Are the Streets, should be situated in the same cultural-political milieu that brought in the ‘crisis of conviviality’ that Sahota details in the novel. In effect, these events can be interpreted as mainly an angry, white and downwardly social mobile response not only to the perceived hypocrisy of neoliberal politics (anti-establishment politics combined with the argument that transnational corporate free trade has not served anyone but corporations and their shareholders), but also the failure of cosmopolitan conviviality (the alleged ‘flatness’ of ostensible cosmopolitanism and political correctness, the protectorate and corrosive product of the liberal left).